2008
DOI: 10.1158/0008-5472.can-07-0824
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gastric Carcinogenesis by Helicobacter pylori Virulence Factors

Abstract: Helicobacter pylori is the strongest known risk factor for gastric adenocarcinoma, and strains that possess the cag secretion system, which translocates the bacterial effector CagA into host cells, augment cancer risk. H. pylori strains that express the vacuolating cytotoxin or the outer membrane protein OipA are similarly associated with severe pathologic outcomes. We previously reported that an in vivo adapted H. pylori strain, 7.13, induces gastric adenocarcinoma in rodent models of gastritis. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
258
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(273 citation statements)
references
References 49 publications
10
258
3
2
Order By: Relevance
“…Abnormal methylations in promoter regions of several genes are induced by H. pylori in gastric mucosa including cell growth-related genes p16(INK4a), p14(ARF), and APC; DNArepair genes, hMLH1, BRCA1, and MGMT; the cell adherence gene E-cadherin; as well as LOX, FLNC, HRASLS, HAND1, THBD, and p41ARC, which are known to be methylated in GC patients [22][23][24]. Individuals with H. pylori infection have increased level of gene methylations, which decrease in the absence of the bacteria, consistent with the notion that methylations are induced by the bacterial infection [4,22,24,25].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Abnormal methylations in promoter regions of several genes are induced by H. pylori in gastric mucosa including cell growth-related genes p16(INK4a), p14(ARF), and APC; DNArepair genes, hMLH1, BRCA1, and MGMT; the cell adherence gene E-cadherin; as well as LOX, FLNC, HRASLS, HAND1, THBD, and p41ARC, which are known to be methylated in GC patients [22][23][24]. Individuals with H. pylori infection have increased level of gene methylations, which decrease in the absence of the bacteria, consistent with the notion that methylations are induced by the bacterial infection [4,22,24,25].…”
Section: Discussionsupporting
confidence: 73%
“…pylori are known to be a major risk factor for GC progression. It causes chronic active inflammation in the gastric mucosa and has the capacity to colonize human stomach persistently [4,5]. Abnormal methylations in promoter regions of several genes are induced by H. pylori in gastric mucosa including cell growth-related genes p16(INK4a), p14(ARF), and APC; DNArepair genes, hMLH1, BRCA1, and MGMT; the cell adherence gene E-cadherin; as well as LOX, FLNC, HRASLS, HAND1, THBD, and p41ARC, which are known to be methylated in GC patients [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PMSS1 harbors the nontoxic s2/m2 variant of VacA, our studies do not allow us to draw conclusions with respect to the role of cytotoxic VacA in gastric pathology. Despite a clear association of toxigenic forms of VacA with an increased risk of peptic ulceration and gastric cancer in humans (30), other experimental studies in rodents have not detected a role for VacA in gastritis (17) or gastric dysplasia and cancer (31,32).…”
Section: Discussionmentioning
confidence: 96%
“…H. pylori colonizes mainly gastric epithelium but may also penetrate the mucus layer reaching pits of gastric glands 9. We have previously shown that fibroblasts may constitute a direct target for H. pylori 10 next to epithelial cells 11, 12…”
Section: Introductionmentioning
confidence: 99%